Editorial - Archivos de medicina veterinaria, Revista (Archivos de Medicina Veterinaria, 2016)
As scientists, we always face the challenging questioning of to trust or believe. However this questioning is not only part of our research when interpreting new analyses and models, it is also part of a continuing struggle when presenting our new information to general public or decision makers. Currently, scientists worldwide, with more or less variation by country of residence, feel overwhelmed when confronting their data and information with decisions of governmental agencies. Governments mostly base their actions on political tendencies believing in what to do instead of trusting quantitative information or simply neglecting evidences for problem solutions. There are several examples of this controversy, a crash of these two apparently different worlds.